Search for a fermiophobic Higgs boson in pp collisions at root s=7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Aguilo, E; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; et al. (2012)
Combined results are reported from searches for a fermiophobic Higgs boson in the γγ WW, and ZZ decay modes in proton-proton collisions at √s = 7TeV. The explored Higgs boson mass range is 110-300 GeV. The data sample corresponds to an integrated luminosity of 4.9-5.1 fb-1. A fermiophobic Higgs boson is excluded at 95% confidence level in the mass range 110-194 GeV, and at 99% confidence level in the mass ranges 110-124.5 GeV, 127-147.5 GeV, and 155-180 GeV.